The Journal of Inflammation - Punchard Neville A; Whelan Cliff J; Adcock Ian (BMC, 2004)
Abstract Welcome to the Journal of Inflammation, the first open-access, peer-reviewed, online journal to focus on all aspects of the study of inflammation and inflammatory conditions. While research into inflammation has resulted in great progress in the latter half of the 20th century, the rate of progress is rapidly accelerating. Thus there is a need for a vehicle through which this very diverse research can be made readily available to the scientific community. The Journal of Inflammation, a peer reviewed journal, provides the ideal vehicle for such rapid dissemination of information. The Journal of Inflammation covers the full range of underlying cellular and molecular mechanisms involved, not only in the production of the inflammatory responses but, more importantly in clinical terms, in the healing process as well. This includes molecular, cellular, animal and clinical studies related to the study of inflammatory conditions and responses, and all related aspects of pharmacology, such as anti-inflammatory drug development, trials and therapeutic developments, etc. All articles published in the Journal of Inflammation are immediately listed in PubMed, and access to published articles is universal and free through the internet.